Estudio axiológico del currículo de Religión Católica de la Educación Primaria = Abweichender Titel: Axiological Study of the Curriculum of Catholic Religion in Primary Education - López-García-Torres, Rocío (Cauriensia, 2025)
The curriculum of each educational stage constitutes the normative framework whose principles and values the schools and institutes ​​assume. They are specified in the planning for each course of the teaching staff of the different subjects, which is later translated into pedagogical action in the classroom. Focusing on the regularly controversial case of the subject about religion, this research analyzes the values ​​in which the new Spanish curriculum for the teaching of Catholic Religion intends to educate. Therefore, an axiological, analytical, and critical study is exposed; the corpus is the legal text of the Resolution of June 21, 2022, of the Secretary of State for Education, by which the curricula of the Catholic Religion teachings are published, corresponding to Pre-school Education, Primary Education, Compulsory Secondary Education and Baccalaureate in Spain, specifically in annex II, "Catholic Religion in Primary Education". The main objective of the work is focused on identifying the values, express and implicit, that this resolution establishes for the stage from 6 to 12 years, according to an indicated axiological model of integral education. This is a documentary research, using the technique of content analysis (Bardin, 2002), of a fundamentally qualitative nature. The results reveal the predominance of religious and social values, followed by moral ones. Significant data is also extracted, such as the scarce presence of corporal and spatial values, and the representation of other values, especially aesthetic and ecological ones, shown as improvable, according to the artistic tradition of Christianity and the recent concerns of the Vatican for the common home, respectively.